MODEL MANAJEMEN KURIKULUM TERPADU BERBASIS NILAI – NILAI RELIGIUS DI MADRASAH - Sri Puji Astutik; Ahmad Thohirin; M. Furqon Wahyudi (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe and analyze an integrated curriculum management model based on religious values implemented in madrasah, particularly at MI Murni Sunan Drajat and MI Sabilillah Lamongan. A qualitative approach with a multisite study design was employed. Data were collected through participant observation, in-depth interviews, and document analysis involving principals, teachers, students, and parents. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that the management of an integrated curriculum grounded in religious values is implemented systematically through the stages of curriculum planning, organizing, implementation, supervision, and evaluation. The integration of religious values is embedded in curriculum objectives, learning materials, instructional processes, assessment practices, and madrasah culture. This approach has a positive impact on students’ religious character formation, discipline, responsibility, as well as improvements in both academic and non-academic achievement. The novelty of this study lies in the formulation of an integrated curriculum management model that positions religious values not merely as an additional learning component, but as both a philosophical foundation and an operational framework across all stages of curriculum management at the primary-level madrasah.